Epidemiological profile of patients undergoing endoscopic retrograde cholangiopancreatography in a reference service in Pará (Research, Society and Development, 2025)
Endoscopic Retrograde Cholangiopancreatography (ERCP) is a minimally invasive procedure that combines endoscopy and fluoroscopy and is widely used for the diagnosis and treatment of pathologies of the biliary and pancreatic systems. Although efficient, it presents risks such as pancreatitis, hemorrhage, and perforation, which justifies the need for epidemiological monitoring and evaluation of clinical outcomes. The objective of this study was to analyze the epidemiological profile and clinical outcomes of patients undergoing ERCP in a referral hospital in Pará in 2024. For this purpose, a prospective, descriptive, and quantitative study was carried out, including 37 patients over 18 years of age, of both sexes, who agreed to participate in the study. Demographic, clinical, and procedure-related data were collected using standardized forms. Statistical analyses were performed using Excel and Epi Info BioEstat 5.0 programs. The results showed a predominance of women (70.27%) and patients over 60 years of age (37.84%). Regarding comorbidities, 56.76% of patients were healthy, while arterial hypertension was the most frequent condition (21.62%). The main indications for ERCP were cholestatic syndrome (64.86%) and choledocholithiasis (29.73%). The success rate in biliary cannulation was 89.19% and stone removal represented 69.7% of the therapies performed. The incidence of labor complications (8.11%) was similar to that reported in other studies (4-10%), confirming the relative safety of the procedure when well performed. Finally, the findings corroborate the national and international literature on the prevalence of choledocholithiasis in women and the elderly, in addition to the efficacy of ERCP as a therapeutic method.